Laser flashing light as a radiation source for lettuce growth - Li, Kun; Cheng, Ruifeng (International Journal of Agricultural and Biological Engineering, 2024)
Relatively lower light intensity and higher energy consumption of electrical lightings in plant factories encourage people to search for new light sources and illuminating patterns. In this study, a laser diffuse system was built to produce laser flashing light (LF) by making high-intensity red and blue light strips (light intensities were 4700 and 1200 μmol/m2·s, respectively) swept reciprocally in the cultivation area. The growth of lettuces (Lactuca sativa var. capitata) was employed to evaluate the feasibility and efficiency of LF. The results showed that LF could maintain the growth of lettuce; however, the plants in this illumination pattern showed an obvious shade avoidance response and a significant decrease in growth compared with the LED continuous illumination (LEDC) control. After 32 d of growth, the leaf fresh mass in LF and LEDC were 32.9 g and 79.9 g, respectively. The leaf area of LF was only 40% of the value in LEDC. Leaf number, leaf width, and root length in LEDC were 40.2%, 78.6%, and 124.4% higher than LF, respectively. On the contrary, leaf length and stem length in LEDC were significantly 7.7% and 32% shorter than LF. Much lower light intensity equivalent to continuous light (66.6 μmol/m2·s) inLF as well as low quantum absorption and utilization efficiency might be the main reason. Further studies are needed to optimize the illuminating pattern related to frequency and duty ratio, based on the photosynthesis parameters of lettuce. Also, the laser diffuse principle and system construction need to be improved to acquire high photon utilization efficiency and light dispersion. Keywords: laser diffusion, high intensity, intermittent light, plant growth DOI: 10.25165/j.ijabe.20241706.8579 Citation: Li K, Cheng R F. Laser flashing light as a radiation source for lettuce growth. Int J Agric & Biol Eng, 2024; 17(6): 86–92.